2014
DOI: 10.1158/2326-6066.cir-13-0112-t
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicle Cargo of Tumor-Associated MUC1 to Dendritic Cells Allows Cross-presentation and Specific Carbohydrate Processing

Abstract: Tumor-associated glycoproteins are a group of antigens with high immunogenic interest: The glycoforms generated by the aberrant glycosylation are tumor-specific and the novel glycoepitopes exposed can be targets of tumor-specific immune responses. The MUC1 antigen is one of the most relevant tumor-associated glycoproteins. In cancer, MUC1 loses polarity and becomes overexpressed and hypoglycosylated. Changes in glycan moieties contribute to MUC1 immunogenicity and can modify the interactions of tumor cells wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 41 publications
3
30
0
Order By: Relevance
“…PD-L1 decreased in the DCs after maturation, as compared with untreated mature DCs or DCs differentiated in the presence of sunitinib. PD-L1 was expressed in microvesicles released by DCs confirming the role of cell particles in delivering remote signaling (37). The phenotypic changes observed in the pazopanib-treated DCs were accompanied with biological behavior consistent with an immune priming effect.…”
Section: Immune Profile Of Mrcc Patients During Tki Treatmentmentioning
confidence: 54%
“…PD-L1 decreased in the DCs after maturation, as compared with untreated mature DCs or DCs differentiated in the presence of sunitinib. PD-L1 was expressed in microvesicles released by DCs confirming the role of cell particles in delivering remote signaling (37). The phenotypic changes observed in the pazopanib-treated DCs were accompanied with biological behavior consistent with an immune priming effect.…”
Section: Immune Profile Of Mrcc Patients During Tki Treatmentmentioning
confidence: 54%
“…Rughetti and colleagues characterized a population of EVs containing the tumor associated MUC1, a glycoprotein that can bind the MHC groove and induce activation of CD8+ T cells, which can influence its processing, in dendritic cells. Importantly, dendritic cells can also internalize MUC1-positive EVs obtained from ascites of patients with stage III or IV ovarian cancer [ 78 ]. It is evident that, by eliminating the lymphocytes that have the ability to recognize and kill tumor cells, or by activating the regulatory suppressive branch of the adaptive response, cancer can escape immune attack and enhance its own survival [ 79 ].…”
Section: Cancer Extracellular Vesicles and The Tumor Microenvironmmentioning
confidence: 99%
“…Employing the Tn-MUC1 glycoform as cancer model glycoantigen, we showed that the structure of the MGL ligand dictates the upcoming intracellular processing. In fact, upon MGL engagement, the large soluble recombinant Tn-MUC1 glycoprotein (Tn-MUC1 16TR ) corresponding to the one shed in vivo by epithelial cancers remained trapped in the endolysosomal/HLAII compartment, while the MUC1 peptide (Tn-MUC1 3TR ), 60 amino acids long, carrying 9 Tn moles colocalized both in HLAII and HLAI compartments [ 16 , 57 ] ( Figure 3(a) ).…”
Section: The Nature Of the Ligand Can Modulate Signals Through Mglmentioning
confidence: 99%